Analisis Dampak Implementasi Komitmen Indonesia di Sektor Jasa Konstruksi dalam Kerangka AFAS - Widyastutik, Widyastutik; Puspitawati, Eka; Fawaiq, Muhammad (Jurnal Ekonomi dan Pembangunan Indonesia, 2014)
The implication of ASEAN Economic Community (AEC) in 2015 is free mobilization of goods, services, labours, and capital among the member countries. This encourages Indonesia to strengthen its commitments on the construction service sector. This study aims to map Indonesia's commitments in the construction service sector under the ASEAN Framework Agreement on Services (AFAS) with Hoekman Index and investigates the impacts on the macroeconomic and sector performances. The GTAP model analysis shows that Indonesia does not gain from the service liberalization, there is only slight increase of macroeconomic and sector performance. A 50% or full liberalization cause few increase on the real GDP. Positive impact of liberalization is only seen in the construction sector itself.